| By "laws of ordinary . . .", I hope you mean associativity of + and *,
commutativity of +, and left and right distributivity of * over +. My proof
follows. To indicate the inverse, I am using a prime, "'", so x'' is the
inverse of the inverse of x.
Lemma 0: (ba)' = a'b'.
Proof: (ba)(ba)' = e (definition of inverse).
ba(ba)' = e (associativity of *).
b'ba(ba)' = b'e (x = y -> zx = zy, because * is a function).
ea(ba)' = b'e (definition of inverse).
a(ba)'= b' (definition of identity).
a'a(ba)' = a'b' (x = y -> zx = zy).
e(ba)' = a'b' (definition of inverse).
(ba)' = a'b' (definition of identity).
Lemma 1: a = a''.
Proof: a'a = e (definition of inverse).
a''a'a = a'' (x = y -> zx = zy).
ea = a'' (definition of inverse).
a = a'' (definition of identity).
Theorem: (a+ab'a)'+(a+b)' = a'.
Proof: (b+a)(b+a)' = e (definition of inverse).
b(b+a)'+a(b+a)' = e ((b+a) was distributed).
b''(b+a)'+a(b+a)' = e (Lemma 1).
((b+a)b')'+a(b+a)' = e (Lemma 0).
(bb'+ab')'+a(b+a)' = e (b' was distributed).
(e+ab')'+a(b+a)' = e (definition of inverse).
a'((e+ab')'+a(b+a)') = a'e (x = y -> zx = zy).
a'(e+ab')'+a'a(b+a)' = a'e (a' was distributed).
a'(e+ab')'+e(b+a)' = a'e (definition of inverse).
a'(e+ab')'+(b+a)' = a' (definition of identity).
((e+ab')a)'+(b+a)' = a' (Lemma 0).
(ea+ab'a)'+(b+a)' = a' (a was distributed).
(a+ab'a)'+(b+a)' = a' (definition of identity).
(a+ab'a)'+(a+b)' = a' (commutativity of +).
|
| Left-multiplying each side of the identity b + a = (b + a) by (a+b)',
and right multiplying by a' gives:
(a+b)'ba' + (a+b)'aa' = (a+b)'(b+a)a'
Noting that addition is commutative, and that x'y = (y'x)', we get:
((ba')'(a+b))' + (a+b)' = a'
(ab'(a+b))' + (a+b)' = a'
(ab'a + ab'b)' + (a+b)' = a'
(a + ab'a)' + (a+b)' = a'
Which is the desired result.
|